2014
DOI: 10.1590/s0036-46652014000300001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Influenza B Virus Outbreak on a Cruise Ship in Brazil 2012

Abstract: In February 2012, an outbreak of respiratory illness occurred on the cruise ship MSC Armonia in Brazil. A 31-year-old female crew member was hospitalized with respiratory failure and subsequently died. To study the etiology of the respiratory illness, tissue taken at necropsy from the deceased woman and respiratory specimens from thirteen passengers and crew members with respiratory symptoms were analyzed. Influenza real-time RT-PCR assays were performed, and the full-length hemagglutinin (HA) gene of influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
1
8
0
2
Order By: Relevance
“…Of 11 hospitalized cases of acute respiratory illness, there were six cases with influenza B virus detected in the nasopharyngeal isolates. 35 In another study by Borborema et al 32 , it was shown that the influenza B virus was the cause of the outbreak (detected in seven individuals with respiratory illness).…”
Section: Online Literature Searchmentioning
confidence: 96%
See 2 more Smart Citations
“…Of 11 hospitalized cases of acute respiratory illness, there were six cases with influenza B virus detected in the nasopharyngeal isolates. 35 In another study by Borborema et al 32 , it was shown that the influenza B virus was the cause of the outbreak (detected in seven individuals with respiratory illness).…”
Section: Online Literature Searchmentioning
confidence: 96%
“…In all, 12 articles presenting evidence on influenza B virus circulation in Brazil for the years 1996-2013 were included. [30][31][32][33][34][35][36][37][38][39][40][41] Details for each of the studies are shown in Supplementary File 1.…”
Section: Online Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In February 2012, an outbreak of respiratory illness occurred on the cruise ship off Brazil, resulting in 16 hospitalizations due to severe ARI and one death. 3 In May 2020, a dual outbreak of pandemic (H1N1) 2009 and influenza A (H3N2) on a cruise ship occurred: of 1,970 passengers and 734 crew members, 82 (3.0%) were infected with pandemic (H1N1) 2009 virus, and 98 (3.6%) with influenza A (H3N2) virus. 4 Four subsequent cases were epidemiologically linked to passengers but no evidence of sustained transmission to the community or passengers on the next cruise was reported.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Mismatches were found between the vaccines and circulating strains throughout the study years, suggesting the vaccines may not have been effective for northern Viet Nam in those years. Table 2).…”
Section: 31516mentioning
confidence: 99%